Studi Kasus Tatalaksana Skabies Melalui Pendekatan Kedokteran Keluarga Pada Pasien Anak Laki-Laki Usia 10 Tahun - Noviana Zara; Zilva Hayati (Pusat Riset dan Inovasi Nasional, 2023)
Scabies is a parasitic infectious disease (Sarcoptes scabiei var. hominis) which is still a public health problem in the world, including Indonesia. Scabies can be transmitted through direct and indirect contact with the greatest prevalence in children, densely populated populations, poor sanitation and hygiene. Symptoms and signs of scabies include papules, vesicles, pustules or nodules accompanied by itching at night with a predilection for a thin epidermal layer. This study is a case report that aims to examine the accuracy in diagnosing and providing pharmacological and non-pharmacological (communication, information and education) treatment of scabies patients. Primary data were obtained through anamnesis (by autoanamnesis and alloanamnesis with the patient's family members) and physical examination by conducting home visits, filling out the family folder, and filling out patient files. The assessment was carried out based on the initial holistic diagnosis, process and end of the visit both quantitatively and qualitatively. In the study, a 10-year-old boy patient was found at the Pediatric Polyclinic at the Dewantara Health Center with complaints of itching all over the body, especially between the fingers, since the last 8 months. Complaints of itching worsen at night so that it disturbs the patient's sleep. The patient has two siblings who live in Dayah with the same complaint and occasionally stay at home with the patient. The patient's mother also had the same complaint. On physical examination, HR: 88x/I, RR: 18x/I, temperature: 36.5°C and nodules were found in the left palmar region of the manus, and canaliculi in the form of white straight lines with papular tips. Management in the form of communication, information and education on environmental sanitation and hygiene as well as pharmacological treatment.